Is Making Divorce Easier Bad for Children? The Long‐Run Implications of Unilateral Divorce - Gruber, Jonathan (Journal of Labor Economics, 2004)
I assess the long‐run implications for children of growing up in a unilateral divorce environment, which increases the ease of divorce by not requiring the explicit consent of both partners. Using 40 years of census data to exploit the variation across states and over time in changes in divorce regulation, I confirm that unilateral divorce regulations do significantly increase the incidence of divorce. Adults who were exposed to unilateral divorce regulations as children are less well educated, have lower family incomes, marry earlier but separate more often, and have higher odds of adult suicide.